2021
DOI: 10.1080/23249676.2021.1961618
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Fogera Plain flood regime due to Ribb Dam construction, Upper Blue Nile Basin, Ethiopia

Abstract: The Fogera Plain, Ethiopia, is affected by recurrent flooding of the Ribb and Gumara Rivers. A large dam on the Ribb River is under construction for irrigation, but also to reduce flooding. We investigated the effects of the dam on the flood regime of the floodplain wetlands using a combination of hydrodynamic and a rainfall-runoff models. The model was calibrated based on inundation maps retrieved from Landsat images. Pre-and post-dam model comparison for 10 years shows that the dam will reduce the flooding e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…A 73-meter-high dam and a diversion weir 30 km downstream to irrigate 15 000 ha of land make up the Ribb River Dam. [95] As a result, from the LULC analysis of three historical periods, it can be concluded that all periods indicated a decline in grazing, shrub lands, and forest area and an increase in cultivated land. This study's investigation of LULC change during 40 years between 1983 and 2022 revealed an increase in cultivated land of 47 541 km 2 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A 73-meter-high dam and a diversion weir 30 km downstream to irrigate 15 000 ha of land make up the Ribb River Dam. [95] As a result, from the LULC analysis of three historical periods, it can be concluded that all periods indicated a decline in grazing, shrub lands, and forest area and an increase in cultivated land. This study's investigation of LULC change during 40 years between 1983 and 2022 revealed an increase in cultivated land of 47 541 km 2 .…”
Section: Discussionmentioning
confidence: 95%
“…A 73‐meter‐high dam and a diversion weir 30 km downstream to irrigate 15 000 ha of land make up the Ribb River Dam. [ 95 ]…”
Section: Discussionmentioning
confidence: 99%